Design of a pedestrian bridge using Warren Truss model - Getial Rivera, Sofia Liliana; Gordillo Plata, Lucía (Boletín Informativo CEI, 2019)
A recent investigation about the pedestrian safety outside Libertad High School shows a problem with the traffic, because when the students and old people try to cross the street, put their life at risk. So, to improve people’s life and to avoid pedestrian accidents, a pedestrian bridge will be designed as an integrative Project, using Warren Truss model. In calculus, integer-differentials equations will be applied; in physics, the sum of forces will be calculated; the area and volume of some structural parts will be found in vector geometry, and finally it will be used AutoCAD software to design the pedestrian bridge in 3D.